Reichsparteitag Nürnberg 1933 NSDAP Propaganda Postkarte Reichsadler... - Uncredited artist. No... (Wikimedia Commons, 1933)
Carte postale ancienne issue de Wikimedia Commons. Titre: Reichsparteitag Nürnberg 1933 NSDAP Propaganda Postkarte Reichsadler Hakenkreuz Nuremberg Nazi Party Congress Postcard Swastika No known copyright restrictions. Nürnberg 1933. Evig das Volk stark das Reich. Postcard promoting and commemorating the Nuremberg Rally (German: Reichsparteitag Nürnberg) in September 1933. Nazi style Reichsadler (German imperial eagle), handshake, etc. No known copyright restrictions. See lighter version. The annual rally of the Nazi Party (NSDAP were large propaganda events, especially after Adolf Hitler's rise to power in 1933. These events were held at the Nazi party rally grounds in Nuremberg, Germany from 1933 to 1938.
Licence Creative Commons Attribution-Share Alike 4.0 via Wikimedia Commons
Keywords: carte postale; image; patrimoine; histoire locale; wikimedia commons